Conical spouted bed segregation composed of sand and Polyethylene/Aluminum composite mixture - Covre, Victor Rocon; Louvem, Renata Falqueto; Melo, Jardel Leno Zancanella; Ribeiro , Daniel da Cunha; Bacelos, Marcelo Silveira (Brazilian Journal of Production Engineering, 2024)
The conical spouted bed is an important gas-solid reactor alternative for the pyrolysis process of LDPE/Al composite, as it provides lower pressure drop and higher turbulence compared to the equivalent fluidized bed. Inert material is added to promote flow regime stability and increase the heat transfer rate. However, this practice can lead to unwanted segregation. Therefore, this research deepens the experimental and computational knowledge of fluid dynamics by predicting the impact of the specularity coefficient on the particle concentration prediction along the spouted bed's conical column. CFD analysis was developed in FLUENT 13 software, applying the Eulerian Granular Multiphase Model (EGMM), Gidaspow drag model, and dispersed k-ε turbulence model. Experiments indicate low segregation, reaffirming the conical spouted bed as an alternative for the process. Initially, an increase in air velocity tends to increase segregation. Even higher levels cause collisions between particles and the wall, altering the regular trajectory and thus reducing segregation. Lower specularity coefficient values yielded better results in CFD simulations, indicating that the system has a low friction value with the wall.
Keywords: Pyrolysis; binary mixture; Computational fluid dynamics; specularity coefficient